The Effect of Ginger Honey and Cocktail Honey Supplementation on Glutathione Levels in Balb/C Female Mice Induced Stress - Umami, Nurrahmi (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the effect of Ginger honey and Cocktail honey supplementation on increasing glutathione levels and to assess the difference in the effect of Ginger honey and Cocktail honey administration on increasing glutathione levels in female Balb/c mice. The intervention in this research is conducted at the Biopharmaca Laboratory of the Faculty of Pharmacy, Hasanuddin University, and the examination of glutathione levels is carried out at the Microbiology Laboratory of Hasanuddin University Education hospital. The method of this research is in vivo research with the pretest-post-test control group. The samples in this study are 25 female Balb/c mice and are divided into five groups (each 5) with one positive control group (swimming activity) and four intervention groups. The provision of intervention in the form of ginger honey is as much as 28 mg/gramBW sample once every day for 14 days. The provision of cocktail honey (containing honey, royal jelly, and bee bread) as for the division of groups is distinguished from the administration dose of 14 mg/gramBW a day on cocktail honey I and 28 mg/ gramBW a day on cocktail honey II. Glutathione levels are examined using the ELISA method, statistical analysis using paired sample T-test. In this research, it is found that administration of ginger honey II containing 33% honey and extract ginger at a dose 28 mg/gramBW (p = 0.031) and cocktail honey II at a dose of 28 mg/gramBW (p = 0.044) given once a day for 14 days can significantly increase glutathione levels with a value of p